Mathematical modelling of continuous formation of multilayer humic-mineral solid components - Kornienko, Yaroslav; Raida, Vasyl; Sachok, Roman; Tsepkalo, Oleksiy (Publishing House of Lviv Polytechnic National University, 2009)
Amathematicalmodel of continuous granulation process of solid multilayer humic-mineral composites in the fluidized bed unit intended for liquid industrial wastes utilization with obtaining of complex granular fertilizers for environmentally safe agriculture was developed and the stabilization terms of the dispersion composition were defined. Розроблено математичну модель безперервного процесу гранулоутворення твердих багатошарових гуміново-мінеральних композитів в апараті псевдозрідженого шару утилізації рідких промислових відходів з отриманням комплексних гранульованих добрив для екологічно безпечного землеробства і визначені умови стабілізації дисперсного складу.
Математичне моделювання безперервного утворення багатошарових гуміново-мінеральних твердих композитів
Keywords: mathematical model; humic-mineral composites; granulation process; liquid wastes; математична модель; гуміново-мінеральні композити; гранулоутворення; рідкі відходи